RUSSIA-AZERBAIJAN: ACK TO THE BEGINNING? - ALIEV, Farkhad (CENTRAL ASIA AND THE CAUCASUS, 2004)
For historical and geographical reasons, under estimation of Russia’s role in the Caucasus as a whole, and in the Southern Caucasus in particular, as well as tension in relations with it are fraught with a great many negative effects irrespective of the foreign policy aims, sympathies, and antipathies of the ruling circles of our republic. The relatively recent events in Azerbaijan, after the Soviet Union disintegrated and our republic gained its independence, can be used as proof of the above. The same applies to Russia: the Kremlin’s right tactics and adequate accents in the Caucasus, including the Southern Caucasus, are of vital importance for Moscow, which wishes to preserve its influence in this strategically important region. Western, or to be more exact, American political, cultural and economic expansion is another-er important factor to be reckoned with when talking about Russian-Azerbaijani relations. “The United States has highly assessed Azerbaijan’s geopolitical potential in a region the Americans regard as strategically important to them. They de-scribe it as a potentially key area and a ‘strong point’ of American policy, not only in the Caucasus, but also in Central Asia, Iran, and the Middle East.”1 Russia’s self-respect is wounded: it has al-ways regarded the Caucasus as the sphere of its interests. Today, however, the United States is holding cultural and economic sway over it in Azerbaijan (and elsewhere). Apart from the statements about a multipolar world that have been heard more and more often since Vladimir Putin came to power in Russia, Moscow unfortunately has nothing to offer as an alternative to the ideology of Atlanticism and market economy on the world-wide scale or at least within the post-Sovi-et space. The two countries established diplomatic relations on 4 April 1992; several months later, on 30 September, their governments signed a free trade and several other agreements. Until Vladimir Putin was elected president, however, the relations could have been described as vague and even negative. In the early 1990s anti-Soviet sentiments dominated in Azerbaijan: gradually they trans-formed into anti-Russian feelings. They were aroused by the Karabakh conflict and concentrated mainly on the person of President of the Soviet Union Mikhail Gorbachev whose position was interpreted as a pro-Armenian one. We should also bear in mind that public opinion was very much affected by the tragic events of January 1990 that took many civilian lives. The blame for this lies on the then leaders of the C.P.S.U. Central Committee. On top of this such facts should be taken into account as “the 336th motor rifle regiment’s direct involvement in ethnic cleansing in the city of Khojaly,”2 as well as participation of Russian troops in the Karabakh hostilities on the Armenian side. This naturally affected the relations be-tween the two countries. I would like to say in all justice that fairly one-sided statements of certain Azerbaijanian political scientists to the effect that in the post-Soviet peri-od the Russian leaders treated our republic badly and that this was responsible for the far from good relations between the two countries are only meant